CORPORATE GOVERNANCE AND SUSTAINABLE DEVELOPMENT GOALS DISCLOSURE IN ENERGY SECTOR - Khoirotun Nikmah; Fani Nadia Listiowati; Wulan Budi Astuti (RISET: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2026)
This study examines the impact of corporate governance mechanisms on the disclosure of Sustainable Development Goals (SDGs) within Indonesian energy sector companies. The variables tested include the proportion of independent commissioners, institutional ownership, and the existence of an audit committee. A quantitative method using panel data analysis and a Random Effects Model, tested with EViews 13 software, was used to collect data from 17 energy sector companies listed on the Indonesia Stock Exchange between 2020 and 2024. The findings show that the audit committee has a positive impact on SDG disclosure. On the other hand, institutional ownership and independent commissioners have a negative but insignificant impact. Sensitivity analysis during the COVID-19 pandemic and post-pandemic periods showed no significant differences in all variables studied. These findings emphasize the importance of effective audit committee oversight in improving sustainability transparency and provide policy implications for the Financial Services Authority in strengthening corporate governance oversight in the energy sector.